[Shipping - Blue Funnel Line : ephemera material collected by the National Library of Australia].
The ephemera collection contains documents of everyday life generally covering publications of fewer than five pages. These may include: advertising material, area guides, booklets, brochures, samples of merchandise postcards, posters, programs, stickers and tickets.
Also available online
Alfred Holt and Company, trading as Blue Funnel Line, was a UK shipping company that was founded in 1866 and operated merchant ships for 122 years, including to Australia. It was one of the UK's larger shipowning and operating companies, and had a significant role in the country's overseas trade and in the First and Second World Wars.
Keywords: Blue Funnel Line -- Miscellanea; Merchant ships -- Australia -- Miscellanea; Shipping -- Australia -- Miscellanea; Printed ephemera -- Australia; Shipping - Blue Funnel Line